1997
DOI: 10.1097/00003072-199712000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Renal SPECT With Tc-99m DMSA in Children With Upper Urinary Tract Infections Using a Triple-Headed Gamma Camera

Abstract: This study demonstrates the superiority of SPECT scanning in detecting kidney lesions in children with UTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…117,189,218 One study compared SPECT DMSA with planar DMSA and found complete agreement. 117 The other two studies compared different scintigraphic agents ( 99m Tc-MAG3 and 123 I-hippuran) with scintigraphy using 99m Tc-DMSA. Both studies reported specificities of 100%; sensitivity was 82% in one and 92% in the other.…”
Section: Static Renal Imagingmentioning
confidence: 99%
“…117,189,218 One study compared SPECT DMSA with planar DMSA and found complete agreement. 117 The other two studies compared different scintigraphic agents ( 99m Tc-MAG3 and 123 I-hippuran) with scintigraphy using 99m Tc-DMSA. Both studies reported specificities of 100%; sensitivity was 82% in one and 92% in the other.…”
Section: Static Renal Imagingmentioning
confidence: 99%
“…Most of the PET tracers have very short half-lives (2± 15 min), but 18 Fluorine has a half-life of 110 min. This allows the preparation of 18 F-¯uorodeoxyglucose (FDG), which enters the cell along with glucose, but is not metabolized and so accumulates in the cell.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…However, in DMSA imaging, SPECT can produce ‘slices’ through the kidney and ‘surface‐rendered’ images of the kidneys, theoretically allowing better detection of defects of uptake (presumed scars). Some studies show a better detection of defects with SPECT than with planar imaging [18,19]. However, the problem with these studies is that the processing involved in the generation of the SPECT images may produce ‘defects’, especially if the kidney function is poor, and it is difficult to be sure if the larger number of defects really represents scarring.…”
Section: Clinical Situationsmentioning
confidence: 99%
“…Diagnostically, SPECT/ldCT nonetheless has several potential benefits in that it provides three-dimensional images of the renal parenchyma in toto, while only approximately three-quarters of the kidney parenchyma are visualized appropriately by planar scintigraphy. Some studies have thus reported that SPECT/ldCT increases sensitivity for detecting renal cortical defects [4,5], while others found no apparent advantage over planar scintigraphy [6], and the exact additional diagnostic benefit of SPECT/ldCT thus remains to be established.…”
Section: Introductionmentioning
confidence: 99%